2024
DOI: 10.5194/acp-24-5837-2024
|View full text |Cite
|
Sign up to set email alerts
|

Influences of sudden stratospheric warmings on the ionosphere above Okinawa

Klemens Hocke,
Wenyue Wang,
Guanyi Ma

Abstract: Abstract. We analyzed the ionosonde observations from Okinawa (26.7° N, 128.1° E; magnetic latitude: 17.0° N) for the years from 1972 to 2023. Okinawa is in the northern low-latitude ionosphere, where the influences of sudden stratospheric warmings (SSWs) on the ionosphere are expected to be stronger than in the mid- and high-latitude ionospheres. We divided the dataset into winters with major SSWs in the Northern Hemisphere (SSW years) and winters without major SSWs (no-SSW years). During the SSW years, the d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…It seems that the relative O 1 amplitude in the TEC map is smaller than 10% at the place of Okinawa (Figure 7). In agreement with the present study, Hocke et al (2024) found that O 1 was enhanced from December to March. They showed that the maximal O 1 amplitudes occurred just after the onset of major SSWs.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…It seems that the relative O 1 amplitude in the TEC map is smaller than 10% at the place of Okinawa (Figure 7). In agreement with the present study, Hocke et al (2024) found that O 1 was enhanced from December to March. They showed that the maximal O 1 amplitudes occurred just after the onset of major SSWs.…”
Section: Discussionsupporting
confidence: 94%
“…The same period of the O 1 component was also found in a spectral analysis of a long-term time series of ground magnetometer data in Honolulu (Love & Rigler, 2014). In addition, the same period has been observed in ionospheric F 2 region electron density maximum NmF2 data at Okinawa (Hocke et al, 2024). The period of O 1 is different from a lunar day (24.84 hr) since the gravitational potential depends on both, the Moon and the Sun.…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations